FAKTOR- FAKTOR YANG MEMPENGARUHI INTEREST OF REVISIT WISATAWAN PADA WISATA UJONG BLANG KOTA LHOKSEUMAWE - Juliana Putri; Fitria Andriani (Jurnal Ekonomi Syariah, Akuntansi dan Perbankan (JESKaPe), 2021)
Traveling is a necessary thing in everyday life, traveling on a tour can eliminate boredom and can remember thoughts of everyday problems. A good tourist spot will greatly affect the desire to make a visit on that tour, and a good tourist spot will be interesting to make a repeat visit on that tour. The research aims to see the effect of service influence, tourism image, tourist attraction and promotion partially and simultaneously on the interests of visiting tourists. This research uses quantitative methods. Sampling combines accidental sampling and purposive sampling, involving 97 tourists as respondents. Data processing using multiple linear regression with IMB 22 statistical tools: The results of data analysis show that service quality (X1) does not have a significant effect on the interest of returning tourists with a significant value of 0.394> 0.05. The results of data analysis show that the tourism image ( X2) has a significant effect on the interest of returning tourists with a significant value of 0.000 <0.05. The results of data analysis show that tourist attraction (X3) has a significant effect on the interest of returning tourists with a significant value of 0.031 <0.05, the results of data analysis show that Promotion (X4) has a significant effect on the interest of returning tourists with a significant value of 0.022 <0.05 on testing service quality, tourism image, tourist attraction, promotion is able to influence the interest of returning visits simultaneously where the significance value is 0.000 <0.05.